Alcohol Dependence and Suicide‐Related Ideation/Behaviors in an Israeli Household Sample, With and Without Major Depression. (7th October 2013) - Shoval, Gal; Shmulewitz, Dvora; Wall, Melanie M.; Aharonovich, Efrat; Spivak, Baruch; Weizman, Avraham; Hasin, Deborah
<x xml:space="preserve">Abstract</x> Background Suicide‐related ideation and behaviors (SRIB) are associated with both alcohol disorders and major depressive disorder (MDD). The objective of this study was to evaluate the relationship of alcohol dependence (AD) and major depression to the risk for lifetime SRIB. Methods Data from a community‐based sample of 1, 237 adult Israeli lifetime drinkers assessed with reliable diagnostic measures were analyzed using logistic regression. Results Lifetime SRIB was reported in 4.7% and was more prevalent among participants with AD (9.0%) than among those without AD (4.1%); p‐value = 0.01. Although both AD and major depression were associated with SRIB (AD: OR 2.2, 95% CI 1.1 to 4.4; MDD: OR 11.4, 95% CI = 6.4 to 20.4), joint analysis showed that AD without MDD increased risk for SRIB as compared to those without AD or MDD (OR 3.1, 95% CI 1.1 to 9.1), but AD did not increase risk among those with MDD (OR 1.1, 95% CI 0.4 to 2.7). Among those with AD, the severity of subclinical depressive symptoms was associated with increased SRIB. Conclusions These findings show that AD increases risk for SRIB among individuals without a history of major depression. Suicidal tendencies may be undetected and underdiagnosed in this group because of the absence of major depression and therefore left untreated. These findings should be considered when adopting suicide prevention or treatment strategies for this high‐risk subpopulation.